Reading Our Relations in the Past and the Future: A Métis Reading of Wahkohtowin in katherena vermette’s A Girl Called Echo (2017–2021) - Erickson, Stephanie (Pawaatamihk)

(untitled) (University of Winnipeg, 2025)
This paper explores Métis author katherena vermette’s graphic novel collection, A Girl Called Echo (2017–2021) for the ways in which it presents Wahkohtowin-centred storytelling. Engaging with Métis history and Métis-specific theory of Wahkohtowin, this reading of vermette’s text draws connections between ancestral history, resurgent action, and futurity. It examines the protagonist’s journey to connect with her ancestors, grow in her connections with her present-day relations, and consider her roles as a descendant of the past and an ancestor of the future. Through an exploration of these relationships, this paper argues for a Wahkohtowin-centred reading of Métis literatures.